Ciprofloxacin Retention in Agricultural Soil - Garrafa, María Victoria (2022)
In the present work, the adsorption and desorption process of the antibiotic Ciprofloxacin (CIPRO) in an agricultural soil was studied through batch experiments. Freundlich´s model satisfactorily described all the experimental data. A high KF value was obtained, 8.52 L(1/n) mg g-1, indicating a high affinity of CIPRO for the soil, with adsorption percentages of 63% in all cases. On the other hand, the desorption was very low, assuming in all cases less than 7% with respect to the amount previously adsorbed. Based on these results, we can affirm that CIPRO presents a low risk of transfer from the soil to other environmental compartments.